From Classroom to Enterprise: Evaluating the Effectiveness of Vocational Education and Skills Development Programmes in Promoting Youth Entrepreneurship in Nigeria - Ebimieowei BARAKABO (Researchparks Publishing, 2026)
The study examined the effectiveness of vocational education and skills development programmes in promoting youth entrepreneurship in Nigeria, with emphasis on enterprise creation, business survival, income generation and employment creation. It addressed the problem that many beneficiaries completed training but failed to convert acquired competencies into viable and sustainable enterprises because of weak institutional support, inadequate finance, poor infrastructure, gender inequalities and regional disparities. The study was anchored on Human Capital Theory, developed by Schultz and Becker, which held that investment in education and training increased productive capacity and economic returns. Method: The study adopted a qualitative review design based on recent empirical studies, official statistics and policy documents on vocational education, skills development and youth entrepreneurship in Nigeria. Evidence was synthesised thematically around programme effectiveness, enabling factors and barriers to enterprise development. The findings showed that relevant curricula, practical training, instructor competence, digital skills, mentorship, access to finance and market linkages improved entrepreneurial outcomes. However, programme impact remained uneven because institutional fragmentation, limited post-training support, costly credit, unreliable infrastructure, gendered occupational barriers and regional inequalities constrained beneficiaries. The evidence also showed that training produced stronger results when combined with finance, industry exposure, mentoring and reliable markets. The study concluded that vocational education had promoted youth entrepreneurship, but training alone had not guaranteed sustainable enterprise performance. Human capital generated greater returns where supportive institutions and business environments enabled beneficiaries to apply their skills. Government agencies, training institutions, financial organisations and private-sector actors should coordinate curricula, practical training, finance, mentorship, digital support and market access, while targeting women, rural youths and persons with disabilities across economic sectors.